Metformin plus PIAF combination chemotherapy for hepatocellular carcinoma - Petrushev, B.; Tomuleasa, C.; Soritau, O.; Aldea, M.; Pop, T.; Susman, S.; Kacso, G.; Berindan, I.; Irimie, A.; Cristea, V. (Experimental Oncology, 2012)
Objectives: Metformin, the most used oral antidiabetic drug for the treatment of type 2 diabetus mellitus, has proved encouraging results when used in the treatment of various types of cancer such as triple-negative breast cancer. Despite compelling evidence of a role of metformin as an anticancer drug, the mechanisms by which metformin exerts its oncostatic actions are not fully understood yet. Therefore, we tried to bring new insights by analyzing the anti-neoplastic effect of metformin for hepatocellular carcinoma-derived stem-like cells treated with conventional combination chemotherapy. Methods: Cancer stem-like cells previusly isolated from a hepatocellular carcinoma biopsy were treated with metformin, PIAF chemotherapy regimen and the combination of these two protocols. Measurements of lipid peroxidation, reduced glutathione, fluorescein diacetate and proliferation rates were determined, apart from the autophagy assay and apoptosis determination by chip flow cytometry. Results: Metformin alone and especially metformin in association with PIAF increases oxidative stress within the cells by increasing the levels of lipid peroxids as well as decreasing the levels of reduced glutathione. The MTT cell proliferation assay showed decreased proliferation rates for the arm treated with metformin and with the combination of drugs in comparison with the control arm, proving high correlation with the oxidative stress results. The autophagy assay and determination of apoptosis by chip flow cytometry confirmed the results obtained in the previous assays. Conclusion: Metformin could be used in chemotherapy treatments to induce reactive oxygen species and increase the cytostatics effects within the tumor cell. Still, further experiments must be carried out on murine models before we can move on and use this drugs in the adjuvant setting for unresectable primary liver cancer.